2017
DOI: 10.1186/s12872-017-0664-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of coronary artery bypass grafting versus stent-PCI for unprotected left main disease: a meta-analysis

Abstract: BackgroundCoronary artery bypass graft (CABG) surgery has traditionally represented the standard of care for left main coronary artery (LMCA) disease. However, percutaneous coronary intervention with stent implantation (PCI) has more recently emerged as a valuable alternative. The long-time awaited results of the largest randomized trials on the long-term impact of PCI versus CABG in LMCA disease, the newly published NOBLE and EXCEL studies, revealed contrasting results. Thus, aim of the present meta-analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 37 publications
2
28
0
1
Order By: Relevance
“…Our recent meta-analysis suggested additional benefit from the use of clinical variables to select the best revascularization strategy. In fact, diabetes was associated with a better performance of CABG over PCI on the long-term clinical success at meta-regression (12). In line with this concept, it was demonstrated that addition of clinical parameters to the mere anatomical evaluation makes risk stratification more effective (14).…”
supporting
confidence: 52%
See 3 more Smart Citations
“…Our recent meta-analysis suggested additional benefit from the use of clinical variables to select the best revascularization strategy. In fact, diabetes was associated with a better performance of CABG over PCI on the long-term clinical success at meta-regression (12). In line with this concept, it was demonstrated that addition of clinical parameters to the mere anatomical evaluation makes risk stratification more effective (14).…”
supporting
confidence: 52%
“…Nevertheless, CABG seems to perform better in specific patients' categories, such as complex anatomical settings or females. On the contrary, PCI performs better in older patients and less diffuse coronary disease (12).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…[10][11][12][13] In addition to the data from single studies, meta-analysis of multiple studies is a major contributor to the evidence of LMCA stenosis treatment. 11,14 India being among the most populated geographies in the world, the cases of LMCA stenosis are also proportionately high in numbers. Based upon this aspect, we decided to evaluate the data of LMCA angioplasty that were performed in our hospital, a tertiary care center in South India.…”
mentioning
confidence: 99%